Competitiveness of human capital (Journal of Economic Research & Business Administration, 2016)
The state invests in person throughout his life from birth to death. These investments are carried out by the state, primarily through the social structure of society: education, health, culture, physical development and recreation and others. These spheres are called to build up the human capi tal that meets the needs of today’s innovative production.According to the new human development Index for the year of 2014, Norway recognized as the most prosperous country in the world. The five most prosperous countries included Australia, Switzerland, the Nether lands and the United States. Russia is in 57th place in the ranking.Сcording to UNDP for 2014 Kazakhstan comes with a high level of development of the HDI, it is within (0,757 ) is 70 place, Russia 57th place in the HDI rating (0.778), Ukraine (0.734) 83 [4];
Keywords: human capital; competitiveness of man; index of human development.